Modeling Tree Growth Taking into Account Carbon Source and Sink Limitations - Hayat, Amaury; Hacket-Pain, Andrew J.; Pretzsch, Hans; Rademacher, Tim T.; Friend, Andrew D. (Frontiers in Plant Science, 2017)
Increasing CO$_2$ concentrations are strongly controlled by the behaviour of undisturbed forests, which are believed to be a major current sink of atmospheric CO$_{2}$. There are many models which predict forest responses to environmental changes but they are almost exclusively carbon source (i.e. photosynthesis) driven. Here we present a model for an individual tree that takes into account also the intrinsic limits of meristems and cellular growth rates, as well as control mechanisms within the tree that influence its diameter and height growth over time. This new framework is built on process-based understanding combined with differential equations solved by the Runge-Kutta-Fehlberg (RKF45) numerical method. It was successfully tested for stands of beech trees in two different sites representing part of a long-term forest yield experiment in Germany. This model provides new insights into tree growth and limits to tree height, and addresses limitations of previous models with respect to sink-limited growth.